2020
DOI: 10.5888/pcd17.200257
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Family Cancer History Knowledge and Communication Among US Adults

Abstract: What is already known on this topic? Knowing one's family cancer history (FCH) plays an important role in cancer prevention. Communicating health histories with relatives can increase awareness about familial cancer risk, and aid health care providers in personalizing cancer prevention recommendations. What is added by this report? This study provides the first nationally representative estimates of FCH knowledge, communication, and confidence completing FCH on medical forms. Findings also identify key demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
2
13
1
Order By: Relevance
“…Specifically, 76.9% of the Chinese American participants had never discussed about their FH of CRC with their PCPs. Compared with a recent study that found that 61% of the general population in the United States had discussed FH of cancer with health care providers (Krakow et al, 2020), it appeared that Chinese Americans were less likely to communicate FH of cancer with PCPs.…”
Section: Discussioncontrasting
confidence: 73%
“…Specifically, 76.9% of the Chinese American participants had never discussed about their FH of CRC with their PCPs. Compared with a recent study that found that 61% of the general population in the United States had discussed FH of cancer with health care providers (Krakow et al, 2020), it appeared that Chinese Americans were less likely to communicate FH of cancer with PCPs.…”
Section: Discussioncontrasting
confidence: 73%
“…Malignancy development is associated with non-modifiable risk factors such as family history and gender, and modifiable risk factors such as smoking, alcohol, physical inactivity, and obesity. Knowing a person's family history can help determine the risk of hereditary diseases, such as cancer, where 5% to 10% of cases are inherited (18,26). In our study, all malignant and premalignant lesions were solid organ related and were present in female patients.…”
Section: Discussionmentioning
confidence: 65%
“…Likewise, having a family history of malignancy has been established as a risk factor for many types of malignancies (17). Knowledge about family history regarding malignancies helps risk assessment of an individual since 5-10% of cases are inherited (18). The American Cancer Society recommends identifying people with a family history and motivating them to engage in genetic counselling alongside earlier and/ or more intensive cancer screening (19).…”
Section: Introductionmentioning
confidence: 99%
“…However, a more recent study suggested that only about one-third (31.1%) of the general population in the US tends to have a thorough knowledge of their family history information. 29 …”
Section: Hereditary Colorectal Cancermentioning
confidence: 99%